Anthropocene futures: People, resources and sustainability. (August 2015) - Knight, Jasper
The sustainable use of environmental resources is an important tenet guiding future governance and management in the Anthropocene. However, the concept of sustainability is based on underlying assumptions of how sustainable development policies are formulated and applied. This commentary describes some of the flaws of 'sustainability' which are that (1) it requires full knowledge of the workings of Earth's multiple physical systems and their sensitivities; and (2) the structures and management tools used by societal actors have low adaptive capacity to address ongoing changes to the physical environment. This commentary considers that societal actors and their future roles are likely to emerge from changing economic patterns, community structures and geopolitical contexts over coming decades. This providing an alternative Anthropocene future to that which is commonly posited, and emphasizes the use and limitations of sustainable development and the societal actors that are concerned with it.